Kesantunan Interogatif Bahasa Jawa dalam Menanyakan Petunjuk Arah - Afrizal, Mohamad; Mijianti, Yerry (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2021)
This research is motivated by someone's unpleasant experience when asking directions in Javanese (BJ). Because it is considered impolite, the answer that person gets is wrong and unpleasant. Therefore, this study seeks to formulate BJ's verbal and nonverbal interrogative politeness in asking directions. The data of this research are in the form of BJ conversations in asking directions. The data were obtained through FGD, interview and experimental. The conversation data is then analyzed deconstructively to find markers of politeness. The conclusion from this research is that the formulation of politeness to ask directions verbally is influenced by a) components, functions, and speech codes, b) short length of speech, c) speech sequence, d) intonation, and e) use of expressions marking politeness. This verbal politeness needs to be supported by nonverbal politeness, namely not driving a vehicle, removing all the attributes that cover the face, and not puffing out the body. Keywords: Javanese language, politeness, interrogative, asking directions